Qualitative Analysis of Factors Affecting Employee Job Satisfaction Using Analytical Hierarchy Process (AHP) at PT. Tirta Perkasa Sejahtera - Adinda Jennifer Pardede; Taufik Andriadi; Indira Shofia; I Made Suparta (International Journal of Economics, Management and Accounting, 2025)
This study seeks to identify and prioritize the factors influencing employee job satisfaction at PT. Tirta Perkasa Sejahtera using the Analytical Hierarchy Process (AHP). The research integrates both literature review and expert judgment to determine factors such as work environment, interpersonal relationships, compensation systems, career development, and work-life balance. AHP was used to analyze pairwise comparison matrices to establish the relative weight of each criterion. The results showed that compensation and career development were the most influential factors, followed by work-life balance, work environment, and interpersonal relationships. The study provides a quantitative basis for management to enhance employee satisfaction and improve organizational performance.